Współczesne autoidentyfikacje mieszkańców Zaolzia - Marcol, Katarzyna (Studia Etnologiczne i Antropologiczne, 2015)
For the residents of Cieszyn Silesia, especially Czech, the establishment of national boundaries along the course of the Olza River in 1920, meant that they had to form a new picture of the world and determine their own place in the community, which also had to be redefined. For Zaolzie residents, the process of constructing their own identity depends on mechanisms of competition, negotiation and power (media, education and administration). It also is a consequence of the recognition of the boundary as something natural and “ever” existent. The clash of different self-identifications is seen on the symbolic level, especially linguistic.